PENGARUH KUALITAS PELAYANAN TERHADAP KEPUASAN DAN LOYALITAS PELANGGAN PADA PT. AGUNG AUTOMALL PEKANBARU - Ramadhan Derizal; Wijayanto Gatot; Promalessy Rika (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2022)
This study aims to determine the effect of Service Quality (X) on Customer Satisfaction (Y) and Customer Loyalty (Z) at PT. Agung Automall Pekanbaru. The population of study was Agung Automall SM. Amin Pekanbaru workshop customers whose numbers are not known with certainly. Sampling technique used was purposive sampling and 100 people were selected to be sampled. Structural Equation Model-Partial Least Square (SEM-PLS) with SmartPLS version 3 was used as methods of data analysis. The results were: 1) Service Quality had a positive and significant effect on Customer Satisfaction; 2) Service Quality had a positive and significant effect on Customer Loyalty; 3) Customer Satisfaction had a positive and significant effect on Customer Loyalty; 4) Service Quality had a positive and significant effect on Customer Loyalty throughwork Customer Satisfaction.Keywords: Service Quality, Customer Satisfaction, Customer Loyalty.